Potential contribution of spinal interneurons to the etiopathogenesis of amyotrophic lateral sclerosis - Goffin, Luca; Lemoine, Damien; Clotman, Frédéric (Frontiers in Neuroscience, 2024)
Amyotrophic Lateral Sclerosis (ALS) designates a group of adult-onset fatal and non-curable neurodegenerative disorders defined as the progressive death of motor neurons (MNs) throughout the central nervous system (CNS). At first, ALS was considered as a MN disease, resulting from cell autonomous mechanisms acting specifically in MNs. Accordingly, data from ALS patients and ALS animal models demonstrated alterations of excitability in multiple neuronal populations including MNs, associated with different cellular perturbations including protein aggregation, RNA metabolism defects, calcium mishandling, modified electrophysiological properties, and autophagy malfunctions. However, experimental evidence rapidly demonstrated the implication of other cell types, including glial cells, in the etiopathogenesis of ALS, through non-cell autonomous mechanisms. Surprisingly, the contribution of pre-motor interneurons (INs), which regulate MN activity and could therefore critically modulate their excitability at the onset or during the progression of the disease, has until now been severely underestimated. Here, we review in detail how spinal pre-motor INs are affected in ALS, and their possible involvement in the etiopathogenesis of the disease.